2022
DOI: 10.1039/d1ma00743b
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic γ-cyclodextrin–fullerene complexes with photodynamic activity

Abstract: Amphiphilic γ-cyclodextrin–fullerene 2:1 complexes (CLFCH complexes) were prepared by high-speed vibration milling of lipophilic tail-grafted γ-cyclodextrin (γ-CD), hydrophilic tail-grafted γ-CD and fullerene C60. The transamidation of γ-CD–fullerene complex having two...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…379 Miki et al reported the preparation of amphiphilic γ-cyclodextrin-fullerene complexes and Sugikawa et al described ROS generation. 375,380 With such molecules, it is also possible to prepare hybrid complexes of C60 and hydrophobic porphyrin by mixing in water in the presence of PEG. The resulting C60-porphyrin NPs are negatively charged and can be dispersed in water.…”
Section: Dovepressmentioning
confidence: 99%
“…379 Miki et al reported the preparation of amphiphilic γ-cyclodextrin-fullerene complexes and Sugikawa et al described ROS generation. 375,380 With such molecules, it is also possible to prepare hybrid complexes of C60 and hydrophobic porphyrin by mixing in water in the presence of PEG. The resulting C60-porphyrin NPs are negatively charged and can be dispersed in water.…”
Section: Dovepressmentioning
confidence: 99%
“…Since Krätschmer and coworkers reported the extraction of C 60 and C 70 from carbon soot by using aromatic solvents in 1990, 1 a number of articial receptors have been extensively developed for the recognition and separation of fullerenes. 2,3 Most traditional macrocyclic hosts and their derivatives, such as g-cyclodextrin (g-CD), [4][5][6][7] calix[n]arenes, [8][9][10][11][12][13] pillar [10]arene, 14 and theoretical cucurbit [9]uril (CB [9]), 15 have shown similar binding affinities to fullerene compounds including C 60 and C 70 . There are still many challenges in efficiently distinguishing C 60 and C 70 through molecular recognition.…”
Section: Introductionmentioning
confidence: 99%